PELATIHAN & SOSIALISASI PENGGUNAAN PORTAL KAJIAN ILMU KEISLAMAN PADA MAJLIS TAKLIM DKM NURUL HUDA - Buhori Muslim (P3M Institut Teknologi Pagar Alam, 2022)
Community service is an obligation that exists in the Tri Dharma Perguruan Tinggi (PT),based on this, the service, conducts Research and Service in South Cianjur, Research and Service isprecisely carried out at DKM Nurul Huda, this service is a continuation of Research on the creationof a recitation portal in the mosque managed by DKM Nurul Huda, DKM Nurul Huda has problemsin informing the study activities it manages which often do not reach the community because thedistance between RT/RW is far apart while the community already has the tools to receive thisinformation in the form of smartphone, so that the servants feel that making a portal is an alternativeto convey information on Islamic studies, another obstacle is Nurul Huda's understanding of DKMtowards SITI, so it is necessary to hold training and socialization on the use and management of thisportal. The method used is to listen, pay attention and practice until the DKM administrators whomanage the recitation are able to operate this portal. and at the end of this service, a goodunderstanding of the management of the portal was produced, the DKM management was able toconvey information, even studies on the portal so that pilgrims who did not come could know the studyand know the material presented by Ustad.